MENGOPTIMALKAN KAPABILITAS INOVASI, KOMPETENSI DAN BUDAYA CATUR PURUSA ARTHA DALAM ERA DIGITAL: PERAN KINERJA UMKM - Sari , Ni Komang Santi Yulia; Utami , Ni Made Satya; Verawati, Yenny; Irwandika, Gede; Vindiyastara, Shella Putri (Publika Citra Media, 2024)
This study aims to determine the effect of innovation capability variables, competence, and catur purusa artha on the performance of MSMEs in Bali Province. The respondent data sampled in this study were MSMEs in Bali Province using a questionnaire method using 100 MSME samples calculated using the Slovin formula. In contrast, the data processing and analysis techniques used SPSS software. The findings of this study indicate that: 1) Innovation capability does not have a significant effect on the performance of MSMEs, 2) Competence has a positive and significant effect on the performance of MSMEs, 3) Catur Purusa Artha has a positive and significant effect on the performance of MSMEs.